2004
DOI: 10.1111/j.1399-3054.2004.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel senescence‐associated gene encoding γ‐aminobutyric acid (GABA):pyruvate transaminase is upregulated during rice leaf senescence

Abstract: The gene Osl2, which is specifically upregulated during leaf senescence in rice (Oryza sativa L. cv. Tainong 67), was cloned and functionally characterized. The protein coding region of the gene consists of 19 exons encoding 516 amino acids, with a putative mitochondrial targeting sequence and conserved sequence of the pyridoxal 5 0 -phosphate-binding domain. The recombinant Osl2 fusion protein over-expressed in Escherichia coli displays pyruvate-dependent g-aminobuty-ric acid (GABA) transaminase (EC 2.6.1.19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 49 publications
(52 reference statements)
2
51
0
4
Order By: Relevance
“…One of the most intriguing metabolites that show an age-related accumulation in both the wild type and old5 is GABA. Studies on Osl2, a mitochondrial GABA transaminase in rice (Oryza sativa) (Ansari et al, 2005), suggested a switch in metabolism at the onset of senescence. Next to that, in plants as well as in animals, the GABA shunt is upregulated in times of high respiratory demand (Sweetlove et al, 2007;Fait et al, 2008).…”
Section: The Old5 Mutation Results In a Metabolite Profile Characterimentioning
confidence: 99%
“…One of the most intriguing metabolites that show an age-related accumulation in both the wild type and old5 is GABA. Studies on Osl2, a mitochondrial GABA transaminase in rice (Oryza sativa) (Ansari et al, 2005), suggested a switch in metabolism at the onset of senescence. Next to that, in plants as well as in animals, the GABA shunt is upregulated in times of high respiratory demand (Sweetlove et al, 2007;Fait et al, 2008).…”
Section: The Old5 Mutation Results In a Metabolite Profile Characterimentioning
confidence: 99%
“…24 Additionally, in the recent years, the possibility that GABA might be involved in regulating plant growth and development has been raised. Several plant development processes has been suggested including pollen tube growth, 25 senescence, 26 reproduction, 25 fertilization 27 and are numerous environmental effects causing a decrease in symbiotic N 2 fixation activity. In many cases it has been assumed that such decrease in N 2 fixation could induce growth retardation of the legume plant as well as the plant demand for symbiotically fixed N. 6 There is a growing body of evidence indicating that symbiotic N 2 fixation of legumes is tightly regulated by the host N-demand which is mediated through N-feedback mechanism.…”
Section: Role Of γ-Aminobutyric Acid (Gaba) In Plantsmentioning
confidence: 99%
“…The amount of GABA in the resulting supernatant was measured by the CE/MS method described above. Pyruvate-dependent GABA-T (GABA-TP) activity was measured according to the method of Ansari et al, 27 with minor modifications. The extract was added to a reaction mixture (pH 8.2) containing 50 mM Tris-HCl, 1.5 mM DTT, 0.5 mM EDTA, 10% glycerol, 10 mM GABA and 0.1 mM PLP.…”
Section: Methodsmentioning
confidence: 99%